Learning Patterns in STEAM Education: A Comparison of Three Learner Profiles - Xiaofang Liao; Heng Luo; Yang Xiao; Lin Ma; Jie Li; Min Zhu (MDPI AG, 2022)
A learner profile is a method of classifying learners through their characteristics. Much of the current research on learner profiles has focused on online learning environments; there is a lack of in-depth category profiling and learning behavior analysis of student profiles in the STEAM context. To address this research demand, this study conducted a cluster analysis based on observed higher-order thinking behaviors, leadership behaviors, and verbal and non-verbal interaction behaviors of 81 primary school students in a STEAM project to explore the differences in learning outcomes, learning perception, and social recognition among different types of learners. The results revealed that STEAM students can be divided into three categories: Thinkers, Speakers, and Followers. There are significant differences between Thinkers and Followers in terms of positive emotions. Speakers and Followers have notable differences in their contributions and active participation. The research results can help teachers acquire a deeper understanding of student types in STEAM and thus provide more relevant and personalized instructional facilitation and class management.